2015
DOI: 10.1088/0951-7715/28/11/3873
|View full text |Cite
|
Sign up to set email alerts
|

Weak-strong uniqueness for measure-valued solutions of some compressible fluid models

Abstract: ABSTRACT. We prove weak-strong uniqueness in the class of admissible measure-valued solutions for the isentropic Euler equations in any space dimension and for the Savage-Hutter model of granular flows in one and two space dimensions. For the latter system, we also show the complete dissipation of momentum in finite time, thus rigorously justifying an assumption that has been made in the engineering and numerical literature.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
103
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 46 publications
2
103
0
Order By: Relevance
“…See [14]. We introduce the concept of dissipative measure-valued solution to the system (1.1) -(1.2) in the spirit of [8] and [9]. Denition 6.…”
Section: Remark 4 In the Denition 3 The Young Measures Are Dened Formentioning
confidence: 99%
See 3 more Smart Citations
“…See [14]. We introduce the concept of dissipative measure-valued solution to the system (1.1) -(1.2) in the spirit of [8] and [9]. Denition 6.…”
Section: Remark 4 In the Denition 3 The Young Measures Are Dened Formentioning
confidence: 99%
“…In the framework of dissipative measure-valued solution (in the spirit of [9]- [8]) we dene the functional …”
Section: Topical Problems Of Fluid Mechanics 3 ______________________mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, measure-valued solutions have been criticized for being too weak, as is apparent from their obvious non-uniqueness (but see the weak-strong uniqueness results in [2,14]). However, recent results by the first three authors jointly with De Lellis [3,4,5] have demonstrated that for the compressible Euler equations (1.1) even entropy solutions (weak solutions satisfying a suitable entropy inequality) may not be unique, thus raising anew the problem of a correct notion of solutions for (1.1).…”
Section: Introductionmentioning
confidence: 99%